2022
DOI: 10.1158/1538-7445.sabcs21-p1-18-28
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-18-28: Phase IV study evaluating effectiveness and safety of talazoparib in patients with locally advanced or metastatic HER2 negative breast cancer and a BRCA1 or BRCA2 mutation (ViTAL)

Abstract: Background: Talazoparib (TALA) is a highly potent PARP inhibitor that has demonstrated clinical benefit in the phase III EMBRACA trial for patients with germline BRCA1 or BRCA2-mutation and a locally advanced or metastatic HER2 negative (HER2-) breast cancer (BC). Methods: ViTAL is an ambispective, multi-center longitudinal, phase IV study that aims to ensure the effectiveness and safety of TALA in the real-world setting among patients with locally advanced or metastatic HER2- BC, with somatic or germline BRCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…This study was the first real-world evaluation conducted in the USA. However, similar studies have been conducted in France, 14 Turkey, 15 and Russia 16 and have been published.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This study was the first real-world evaluation conducted in the USA. However, similar studies have been conducted in France, 14 Turkey, 15 and Russia 16 and have been published.…”
Section: Discussionmentioning
confidence: 52%
“…Findings from the real-world US study were also similar to those reported in the phase IV ViTAL study in France, which included 86 patients with g BRCA m HER2- LA/mBC, as the median TTF of talazoparib for US patients was 8.5 months and the median time to treatment discontinuation, defined as the time between the date of the first dose of talazoparib and the date of last dose or death, for patients in the French study was 8.6 months. 14 No difference was observed according to HR status for either study. However, the median rwPFS and rwORR for talazoparib were more favorable in this real-world US study versus those observed in small real-world studies conducted in Turkey ( n = 47) and Russia ( n = 24).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therapy discontinuation because of adverse events was rare (4.3 %) [41]. The initial results of the phase IV ViTAL trial report a median duration of talazoparib treatment of 9 months as well as a low discontinuation rate due to adverse events (8.0%) [42].…”
Section: Routine Use Of Parp Inhibitors To Treat Advanced Breastmentioning
confidence: 99%
“…Therapieabbrüche aufgrund von Nebenwirkungen waren selten (4,3 %)[41]. Erste Ergebnisse der Phase-IV-ViTAL-Studie zeigen eine mediane Behandlungsdauer mit Talazoparib von 9 Monaten und ebenfalls eine geringe Abbruchquote aufgrund von Nebenwirkungen (8,0%)[42].Leitlinien und Empfehlungen zur molekularen Diagnostik und TherapieIn ihren im Jahr 2022 aktualisierten Empfehlungen zur Diagnostik und Therapie früher und fortgeschrittener Mammakarzinome hat die Kommission Mamma der Arbeitsgemeinschaft Gynäkologische Onkologie e. V. (AGO) erneut den höchsten Empfehlungsgrad für die Durchführung einer BRCA1/2-Genuntersuchung erteilt bei: 1. jeder therapeutischen Relevanz (z. B. PARPi) und 2. möglicher erblicher Belastung für ein Mamma-und/oder Ovarialkarzinom entsprechend der Familienanamnese und Eigenanamnese (einschließlich TNBC vor dem 60.…”
unclassified